2018
DOI: 10.18632/oncotarget.25725
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tools in the differential diagnosis of giant cell-rich lesions of bone at biopsy

Abstract: The diagnosis of giant cell-rich lesions of bone can be challenging if radiological findings are ambiguous and tissue of the biologically deciding component is underrepresented in biopsy specimens. The frequent association of giant cell tumor of bone (GCT) and chondroblastoma (CB) with (secondary) aneurysmal bone cysts (ABC) may further impede correct classification. The present study evaluates the potentials and limitations of mutation-specific histone H3.3 and DOG1 immunohistochemistry, Sanger-/next generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…that are commonly mutated in cancer. As described before [32][33][34] , Target enrichment was conducted by means of the GeneRead DNAseq Panel PCR V2 Kit (Qiagen). Purification and size selection steps were processed utilizing Agencourt AMPure XP magnetic beads (Beckman Coulter).…”
Section: Genes (Akt1 Alk Ar Braf Ctnnb1 Ddr2 Egfr Erbb2 Fgfr3mentioning
confidence: 99%
See 1 more Smart Citation
“…that are commonly mutated in cancer. As described before [32][33][34] , Target enrichment was conducted by means of the GeneRead DNAseq Panel PCR V2 Kit (Qiagen). Purification and size selection steps were processed utilizing Agencourt AMPure XP magnetic beads (Beckman Coulter).…”
Section: Genes (Akt1 Alk Ar Braf Ctnnb1 Ddr2 Egfr Erbb2 Fgfr3mentioning
confidence: 99%
“…In silico tools to predict the potential deleterious impact of detected variants. The potential impact of NGS-detected variants in the coding regions was predicted using following in silico tools as reported [32][33][34] : PolyPhen-2 (v2.2.2r398) 35 , Protein Variation Effect Analyzer (PROVEAN; v1.1.3) 36 , Sorting Intolerant From Tolerant (SIFT; Ensembl 66) 37,38 , Mutation Assessor (release 3) 39 and Combined Annotation Dependent Depletion (CADD; v.1.3) 40 . The PolyPhen-2 method utilizes physical and evolutionary comparative considerations to predict amino acid changes on protein structure and function.…”
Section: Genes (Akt1 Alk Ar Braf Ctnnb1 Ddr2 Egfr Erbb2 Fgfr3mentioning
confidence: 99%
“…Differential diagnosis includes primarily giant cell tumor of bone. Recent genetic and immunohistochemistry studies [ 3 ] have defined a p.Lys36Met substitutions in H3F3B gene on chromosome 17 in about 98% of chondroblastomas, also resulting in the immunohistochemical expression of H3F3B, that distinguishes it from giant cell tumor of bone which presents a H3F3A [ 4 ] mutation and from other mimickers.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Rehkamper et al 23 A similar study done by Ali et al 20 , studied expression for DOG 1 and multiple other immunohistochemical markers in chondroblastoma, giant cell tumors and aneurysmal bone CYST. The study showed positive results for DOG 1 in all the 3 cases of chondroblastomas.…”
Section: Discussionmentioning
confidence: 93%
“…The large specimens show positivity in majority of the cases which may be focal or weak. However smaller biopsy samples can be negative for DOG 1 and clinical, radiological, and histological features remains the gold standard for the diagnosis of this entity with DOG 1 providing a supportive role in difficult cases 23 .…”
Section: Resultsmentioning
confidence: 99%